2021
DOI: 10.21608/mvmj.2021.66416.1040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary Spirulina (arthrospira) platensis on growth performance, gene expression and antioxidant status of quail challenged with salmonella enteritidis.

Abstract: To investigate the effect of dietary Spirulina platensis supplementation on growth performance, organ colonization, expression of inflammatory-related genes, and antioxidant status in quail challenged with Salmonella enteritidis. Design: Randomized controlled experimental study. Animals: hundred eighty-seven-day-old Japanese quail. Procedures: birds were randomly allocated into 6 equal groups. G1, G2, and G3: non challenged and fed abasal diet supplemented with Spirulina at 0, 1, and 2 g/kg diet, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The total polyphenols and flavonoids of SP in the present study are high enough to augment the antioxidant activity of the SP (29.2%, Table 1 ), and this consequently linearly improved the redox status of layers when fed on incremented levels of the SP ( Table 4 ). Furthermore, the increased SP levels in layer diets linearly reduced the inflammation as displayed in our study ( Table 5 ) and reported in other studies [ 63 , 64 ]. It was reported that phenolic compounds and flavonoids can terminate the chain reaction of ROS and similar products before seriously affecting cell viability [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…The total polyphenols and flavonoids of SP in the present study are high enough to augment the antioxidant activity of the SP (29.2%, Table 1 ), and this consequently linearly improved the redox status of layers when fed on incremented levels of the SP ( Table 4 ). Furthermore, the increased SP levels in layer diets linearly reduced the inflammation as displayed in our study ( Table 5 ) and reported in other studies [ 63 , 64 ]. It was reported that phenolic compounds and flavonoids can terminate the chain reaction of ROS and similar products before seriously affecting cell viability [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…IOP Publishing doi:10.1088/1755-1315/1271/1/012081 6 IL-10 mRNA relative expression ratio in this study showed an increase in the spleen of treated rats compared to controls at 12 and 24 weeks of age (figure 1). Although not significantly different, the increment in the age 12 and 24 weeks in our study aligns with the study that used S. platensis supplementation in quail exposed to Salmonella enteritidis [29]. That study shows an increase in the gene expression of the anti-inflammatory cytokine IL-10.…”
Section: Discussionsupporting
confidence: 90%
“…That study shows an increase in the gene expression of the anti-inflammatory cytokine IL-10. Modifying gene expression in the challenged treated groups demonstrated S. platensis anti-inflammatory and protective effects [29]. S. platensis contains C-phycocyanins and β-carotene, which can inhibit NF-κB activity and reduce TNF-α.…”
Section: Discussionmentioning
confidence: 94%
“…The effectiveness of Spirulina’s antibacterial actions in vivo was assessed by Abd El-Dayem et al. ( 56 ) as adding 1 and 2 g of spirulina per kg of diet significantly increased growth performance, antioxidant levels, and the production of the anti-inflammatory cytokine (IL-10) while reducing organ colonization and gene expressions of IL-6, IL-1ß, and TNF-α as compared to positive and negative control groups.…”
Section: Anti-pathogenic Effects Of Spirulina Platensismentioning
confidence: 99%